Immersive Technologies in Museums: A Scoping Review of Cognitive Outcomes Related to Visitor Attention, Engagement, and Learning - Lee, Jun Choi; Piao, GuiCheng; Rehman Ullah, Khan (The Elite Scientific Forum, Pakistan., 2025)
The integration of immersive technologies—such as virtual reality (VR), augmented reality (AR), and mixed reality (MR)—has transformed the landscape of museum experiences from passive observation to interactive, visitor-centered engagement. This scoping review systematically maps the literature on the cognitive impacts of immersive technologies in museum settings, with a focus on attention, engagement, and learning outcomes. Following the PRISMA-SCRA guidelines and Arksey and O’Malley’s framework, 66 peer-reviewed studies published between 2013 and 2024 were analyzed. The findings reveal that immersive technologies significantly enhance visual and auditory attention, emotional and cognitive engagement, and memory retention, especially when grounded in cognitive frameworks such as Flow Theory, Cognitive Load Theory, and Dual-Coding Theory. Virtual reality emerged as the most frequently studied modality, particularly in facilitating episodic memory and spatial attention. Despite these benefits, the review highlights critical gaps in the field, including limited inclusion of neurodiverse and elderly visitor groups, inconsistent cognitive outcome measures, and underutilization of real-time assessment tools like eye-tracking. This review underscores the need for inclusive, theoretically informed, and empirically rigorous approaches to immersive exhibit design that align with cognitive and educational principles.